Akulturasi Budaya pada Makam Syekh Syamsuddin Al-Wasil Setono Gedong Kediri Abad 16 - Nurul Baiti Rohmah (Historia Madania: Jurnal Ilmu Sejarah, 2022)
This study aims to determine the condition of Kediri during the transition from Hindu-Buddhist to Islam which is the background of cultural acculturation at the tomb of Sheikh Syamsuddin Al-Wasil Setono Gedong. In this study, the authors used historical research methods with four stages, namely, heuristics, verification, interpretation, and historiography. The result of this research is that the transition period is the situation behind the acculturation of culture and the expansion of Demak to Majapahit which at that time in Daha was one of the causes of the shift from the Hindu-Buddhist era to Islam. One form of acculturation discussed in this study is the acculturation that occurred at the tomb of Sheikh Syamsuddin Al-Wasil Setono Gedong. The acculturation is contained in the cupola/wall around the tomb, gate, lotus and sunflower motifs, grave first, and inscriptions on the walls around the tomb.